Characterizing the interfacial fracture energy of stiff islands on stretchable films. (9th August 2022) - Lin, Jui-Chi; Tsai, Jia-Lin
Abstract: This study characterized the interfacial fracture energy of stiff islands deposited on a thermoplastic polyurethane (TPU) film. The film can deform by >200%. The film was stretched using a designed fixture, and the fracture behaviors of the islands were observed using a microscope. The island–substrate interface debonding lengths associated with different levels of substrate strain were determined in the stretching tests. Because the stretchable film was a nonlinear material, the Ogden model was employed to characterize the nonlinear constitutive relation. Through the tensile tests, the material parameters in the Ogden model were determined using the reduced-gradient optimization method. On the basis of the measured debonding lengths, a finite element model was generated for the nonlinear properties of the film, and the energy release rates at the crack tip were calculated using the J -integral method. The energy release rates, representing the interfacial fracture energy, were calculated on the basis of the arrested crack associated with different crack lengths. Results reveal that the interfacial fracture energy increased from 0.14 to 0.91 kJ/m 2 as the debonding length increased. The behavior is related to the rising resistance curve in TPU materials. In addition, the shearing-dominated mode slightly decreased as the debonded length increased in the stretching tests.